Supervisi Edukatif Kolaboratif: Membangun Kapasitas Guru di Era Society 5.0 - Putri, Dian Erika; Timan, Agus (Universitas Negeri Malang, 2024)
Abstract The challenge of mastering technology in the learning process in the era of Society 5.0 has implications for efforts to increase teacher capacity to provide active and innovative learning. The principal as a supervisor is needed to provide direction and motivation for teachers. The research was conducted with the aim of analyzing collaborative educational supervision in building teacher capacity in the era of society 5.0. Using a systematic literature review with a descriptive qualitative approach, data collection was carried out by searching for reference sources that were relevant to the discussion. Data analysis using the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) model through a series of identification, screening, and obtaining appropriate data. The results of this research are: (1) an approach that can be used as an educational supervision activity is to use lesson study, MGMP, and school communities in coaching efforts for teachers to improve the learning process actively and innovatively, (2) it is important for teachers to increasing Technological Pedagogical Content Knowledge (TPACK) competence, (3) there are six strategic plans for increasing teacher pedagogical competence: optimizing leader performance, optimizing collaboration between teachers, a collaboration between teachers and students, optimizing external support, optimizing teacher pedagogical development, and increasing teacher collaboration, students, and parents Abstrak Tantangan penguasaan teknologi dalam proses pembelajaran di era society 5.0 berimplikasi pada upaya peningkatan kapasitas guru untuk memberikan pembelajaran yang aktif dan inovatif. Kepala sekolah sebagai supervisor dibutuhkan untuk memberikan arahan dan motivasi bagi para guru. Penelitian dilakukan dengan maksud untuk menganalisis supervisi edukatif secara kolaboratif dalam membangun kapasitas guru di era society 5.0. Menggunakan jenis kajian literatur sistematis (systematic literature review) dengan pendekatan kualitatif deskriptif, pengumpulan data dilakukan melalui pencarian sumber-sumber referensi yang relevan dengan pembahasan. Analisis data dengan menggunakan model Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) melalui serangkaian identifikasi, screening dan mendapatkan data yang sesuai. Hasil dari penelitian ini adalah: (1) pendekatan yang dapat digunakan sebagai kegiatan supervisi edukatif adalah dengan menggunakan Lesson Study, MGMP maupun komunitas sekolah dalam upaya pembinaan bagi para guru untuk aktif meningkatkan proses pembelajaran dengan aktif dan inovatif, (2) penting bagi guru untuk meningkatkan kompetensi Technological Pedagogical Content Knowledge (TPACK), (3) terdapat enam rencana strategis peningkatan kompetensi pedagogik guru: mengoptimalkan kinerja pemimpin, mengoptimalkan kolaborasi antar guru, kolaborasi antara guru dan siswa, mengoptimalkan dukungan eksternal, mengoptimalkan pengembangan pedagogi guru, dan meningkatkan kolaborasi guru, siswa, dan orang tua.